2006
DOI: 10.1111/j.1574-6968.2006.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

The presence of major world-wide clones for phage type 4 and 8Salmonella entericaserovar Enteritidis and the evaluation of their virulence levels by invasiveness assaysin vitroandin vivo

Abstract: Seventy-seven animal isolates of Salmonella enterica serovar Enteritidis (S. Enteritidis) obtained from the United States were analyzed by phage typing and pulsed field gel electrophoresis (PFGE). Thirty-nine strains were found with phage types (PT) 4, 8, and 13a. When the chromosomal DNA of these 39 isolated strains with PT4, 8, and 13a were digested with XbaI, SpeI and NotI, followed by PFGE analysis, 28 strains were found with a pattern combination of X4S4N4, which was the major subtype. When PFGE patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
3
15
1
Order By: Relevance
“…Fewer studies have been conducted to determine differences in invasiveness of field isolates of S. Enteritidis (Pan et al, 2009;Pang et al, 2006;Solano et al, 1998). Although these studies have shown that not all isolates of S. Enteritidis have similar cell invasive potential, only limited numbers of isolates recovered mostly from human, animal, food and the environment were tested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fewer studies have been conducted to determine differences in invasiveness of field isolates of S. Enteritidis (Pan et al, 2009;Pang et al, 2006;Solano et al, 1998). Although these studies have shown that not all isolates of S. Enteritidis have similar cell invasive potential, only limited numbers of isolates recovered mostly from human, animal, food and the environment were tested.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of phage types, geographical origins or source of isolation, S. Enteritidis is one of the most genetically homogeneous serotypes of Salmonella and as a result is poorly discriminated by the commonly used genetic subtyping methods, such as phage typing, pulsed field gel electrophoresis or comparative genomic hybridization microarrays (Betancor et al, 2009;Botteldoorn et al, 2010;Hudson et al, 2001;Liebana et al, 2001;Malorny et al, 2008;Morales et al, 2005;Olsen et al, 1999;Pan et al, 2009;Pang et al, 2006;Porwollik et al, 2005;Saeed et al, 2006;Swaminathan et al, 2001). Because of its greater discriminatory capacity, MLVA was used to assess the genetic similarity among S. Enteritidis isolates tested in this study Cho et al, 2007;Malorny et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we examined the ability of Campylobacter jejuni strains isolated from the caecal contents of broilers to adhere to and invade the cells of the INT-407 human intestinal cell line and determined the association with the presence of certain virulence genes which affect on poultry colonization [43,44] and the adherence and invasion abilities of Campylobacter jejuni isolates. The adherence and invasion abilities of the caecal isolates varied considerably, from invasive levels similar to that of [6,25,33]. Even though the process of Campylobacter adhering to and invading INT-407 human intestinal epithelial cells in culture does not exactly mimic the process in vivo, the cell culture model allowed us to determine the relative adherence and invasion abilities of the caeca isolates in comparison to well-studied human clinical strain C. jejuni 81116.…”
Section: Presence Of the Putative Virulence-associated Genesmentioning
confidence: 99%
“…3 %) were identified as PT 8/7. This phage type is mainly associated with chicken eggs [3] and is not known for particularly high virulence [4] or pathogenicity [5].…”
Section: Introductionmentioning
confidence: 99%